A Quaker Forty-niner : the Adventures of Charles Edward Pancoast on the American Frontier - Pancoast, Charles Edward (University of Pennsylvania Press, 2016)
A dramatic, first-hand account of the pioneering life in the West--steamboating on the Missouri and the gold rush to California.